Hi Tech versus Hi Touch: The Digitalisation of Asnafpreneurs in Perlis - Abdul Rahim, Razinda Tasnim; Md Noor, Nur Syamilah; Muhammad Zuki, Mohd Faizuddin; Noor Azman, Farah Mastura; Mohd Yusuf, Bibi Noraini (International Journal of Business and Technopreneurship (IJBT), 2023)
Digital technology has forced entrepreneurs and businessmen to reconsider their business models. Although research on entrepreneurial intention and business models is gaining attention, there is still a large knowledge gap in both fields. As we know, Perlis is one of the states in Malaysia that is a developing economic state. Most Perlis people are working in agriculture, farming, and running businesses. Parallelly, the COVID-19 pandemic contributed to the transformation of societies involving the Industrial Revolution 4.0 (IR 4.0). The lifestyles of societies employed the adoption of digital technology. Thus, this study aims to investigate the issue of product marketability and assist rural entrepreneurs in improving their digital competencies according to modern standards. In this study, researchers are specifically implementing the transformation of channels of digitalisation on business model practice among asnaf in Perlis. Several channels or platforms, such as social media, business websites, and online delivery applications, are emphasised. The aim of this study is to foresee the business model practices among asnaf regarding their product, promotion, and delivery activities. In addition, this study employed a qualitative method. The data collected was among asnafpreneurs that run the food and beverage industry in Perlis. Eight instruments have been developed based on Business Model Canvas (BMC), and these instruments assist the researchers in producing expected themes. Furthermore, this study exposed the common platforms used by the asnafpreneurs as mentioned in the results. At the end of this study, a digitalisation asnafpreneurs model is presented and discussed. Several limitations and recommendations for future research are suggested.